Hypernatremia in hyperosmolar hyperglycemic syndrome - Blas-Macedo, Jorge; Blas-Soto, Viridiana (Revista Médica del Instituto Mexicano del Seguro Social, 2017)
We report the case of a 82 year-old woman with hyperosmolar hyperglycemic state (HHS) associated with hypernatremia, who was treated using 0.2 % sodium chloride in 5 % dextrose in water which resulted in the amelioration of the neurological symptoms in a short period of time, followed the decrease in serum glucose and the serum sodium, consequently the serum osmolality. We discuss the advantages and usefulness of 0.2 % sodium chloride in 5 % dextrose in water in this syndrome and emphasize its importance in the treatment. We reviewed the literature on HHS and we assume that this case reported was treated with hypotomic solution without subsequent neurological damage.